Lepanthes gerardensis (Orchidaceae), una nueva especie de Costa Rica - Blanco, Mario A. (2016)
Lepanthes gerardensis from north-central Costa Rica is described and illustrated. It is most simi- lar to the Mexican L. ancylopetala Dressler, from which it differs in shorter habit, petiolate leaves with broadly elliptic blades, and different lip shape. It appears to be a specialized twig-epiphyte.